2015
DOI: 10.5114/pm.2015.49999
|View full text |Cite
|
Sign up to set email alerts
|

Chosen risk factors for osteoporosis and the level of knowledge about the disease in peri- and postmenopausal women

Abstract: IntroductionOsteoporosis as a chronic disease, affecting especially women in postmenopausal age, is an important, social and economic health problem especially of women of today's world. The aim of the study was to assess the level of knowledge of women in the peri- and postmenopausal period about the prevention of osteoporosis and show the influence of chosen risk factors on the level of this knowledge.Material and methodsA group of 300 women aged 45-65, being patients of healthcare centres in Chełm, Lublin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…Our results indicate a positive association between knowledge scores and education level as well as total family monthly income. A similar association between education, socio-economic status and knowledge scores has been reported by other studies ( 32 – 34 ) . The positive influence of sociodemographic factors indicates that education and socio-economic status are important factors that should be considered while designing osteoporosis awareness programmes, especially in India.…”
Section: Discussionsupporting
confidence: 90%
“…Our results indicate a positive association between knowledge scores and education level as well as total family monthly income. A similar association between education, socio-economic status and knowledge scores has been reported by other studies ( 32 – 34 ) . The positive influence of sociodemographic factors indicates that education and socio-economic status are important factors that should be considered while designing osteoporosis awareness programmes, especially in India.…”
Section: Discussionsupporting
confidence: 90%
“…In the study of Okumuş et al (17) on 100 women, it was found that the level of knowledge about osteoporosis was insufficient. Considering the studies abroad; In the study of Janistewska et al (18) with 300 women aged 45-65, the average score of the participants in the OKT nutrition group was found to be 9.27, which was below the average we obtained in our study. However, the average score of the exercise group (13.93) and the average score of the total score (15.71) were higher than our study.…”
Section: Discussioncontrasting
confidence: 89%
“…On the other hand, the results of the research performed on 300 Polish women aged 45-65 obtained by Janiszewska et al . [28] showed that 41.7% of the examined women had sufficient knowledge about tobacco smoking as an osteoporosis risk factor. Alarming conclusions were presented by Wahba et al .…”
Section: Discussionmentioning
confidence: 99%